Reading the Epistle of James a resource for students - Mason, Eric Farrel 1969-; Lockett, Darian R. (SBL Press, 2019)
"This volume addresses major issues for interpretation of the Epistle of James in sixteen chapters designed especially for students or others undertaking serious study of this letter for the first time. Topics addressed include possible sources and backgrounds utilized by the author of James, the genre of the book and its literary structure, and major theological themes in James. Three chapters address the book's reception in the early church, the relationship between the epistle and the historical James, and major Catholic and Protestant interpretations of the book in the Reformation era"--
Keywords: Bibel -- Jakobusbrief; Bible / James / Criticism, interpretation, etc; Bible / James; Criticism, interpretation, etc; Aufsatzsammlung